Biochemical and molecular characterization of an acido-thermostable endo-chitinase from Bacillus altitudinis KA15 for industrial degradation of chitinous waste. (September 2020) - Asmani, Katia-Louiza; Bouacem, Khelifa; Ouelhadj, Akli; Yahiaoui, Merzouk; Bechami, Sofiane; Mechri, Sondes; Jabeur, Fadoua; Taleb-Ait Menguellet, Kahina; Jaouadi, Bassem
Abstract: This paper reports the isolation and identification of an acido-thermostable chitinase (ChiA-Ba43) which was purified, from the culture liquid of Bacillus altitudinis strain KA15, and characterized. Purification of ChiA-Ba43 produced a 69.6-fold increase in the specific activity (120, 000 U/mg) of the chitinase, with a yield of 51% using colloidal chitin as substrate. ChiA-Ba43 was found to be a monomeric protein with a molecular mass of 43, 190.05 Da as determined by MALDI-TOF/MS. N- terminal sequence of the first 27 amino-acids (aa) of ChiA-Ba43 displayed homology to chitinases from other Bacillus species. Interestingly, ChiA-Ba43 exhibited optimum pH and temperature of 4–5.5 and 85 °C, respectively. Thin-layer chromatography (TLC) showed that the final hydrolyzed products of the enzyme from chitin-oligosaccharides and colloidal chitin are a mixture of (GlcNAc)2, (GlcNAc)3, (GlcNAc)4, and (GlcNAc)5, which indicates that ChiA-Ba43 possesses an endo -acting function. More interestingly, compared to ChiA-Mt45, ChiA-Hh59, Chitodextrinase®, N -acetyl-β-glucosaminidase®, and ChiA-65, ChiA-Ba43 demonstrated a high level of catalytic efficiency and outstanding tolerance towards various organic solvents. The chiA-Ba43 gene (1332 bp) encoding ChiA-Ba43 (409 aa) was cloned, sequenced, and expressed in Escherichia coli strain HB101. The biochemical properties of the recombinant chitinase (rChiA-Ba43) were equivalent to those of the natively expressed enzyme. These properties make ChiA-Ba43 an ideal candidate for industrial bioconversion of chitinous waste. Graphical abstract: Image 1 Highlights: Purification of chitinase (ChiA-Ba43) from Bacillus altitudinis strain KA15 was carried out. Optimum pH and temperature values for activity were pH 4 and 85 °C, respectively. Kinetic parameters and TLC hydrolysis products of ChiA-Ba43 enzyme were studied. ChiA-Ba43 is a potential candidate for industrial degradation of chitinous waste. The chiA-Ba43 gene encoding ChiA-Ba43, was cloned, sequenced and expressed in E. coli.